Recent Trends in Information Reuse and Integration - Özyer, Tansel.; Özyer, Tansel.; Kianmehr, Keivan.; Kianmehr, Keivan.; Tan, Mehmet.; Tan, Mehmet. (Springer Vienna : Imprint: Springer, 2012)
The present text aims at helping the reader to maximize the reuse of information. Topics covered include tools and services for creating simple, rich, and reusable knowledge representations to explore strategies for integrating this knowledge into legacy systems.  The reuse and integration are essential concepts that must be enforced to avoid duplicating the effort and reinventing the wheel each time  in the same field. This problem is investigated from different perspectives. in organizations,  high volumes of data from different sources form a big threat for filtering out the information for effective decision making. the reader will be informed of the most  recent advances in information reuse and integration.